2005
DOI: 10.1159/000085954
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Pituitary and Adipose Tissue after Hypothalamic Denervation in the Female Rat

Abstract: Neonatal administration of monosodium glutamate (MSG) to rats produces severe lesions in certain hypothalamic nuclei, with repercussions in different neuroendocrine axes, and serves as a model for their study. In addition, adipose tissue, as a target organ, is known to be directly related to several neurondocrine axes. We used 21-day-old female Sprague-Dawley rats that had received a neonatal treatment with MSG (4 mg/g body weight, i.p., from day 2 up to day 10 of age) in addition to control rats (injected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(54 reference statements)
0
2
0
1
Order By: Relevance
“…These measurements were recorded and processed automatically, and the following parameters were then calculated: volume density (VD = sum of adipocyte area/RA), cell density (CD = number of adipocytes/RA), and cellular size (CS; expressed in lm 2 ). As RA represents the total area were cells were scored, the division of the sum of the individual cell areas by the RA yielded VD, a parameter representing an estimate of cell mass according to generally accepted criteria [40]. The number of cells (CD) was calculated by dividing the immunostained area of the adipose tissue by the mean individual cell area.…”
Section: Experiments 3: Omental Adiposity Characteristics and Functionmentioning
confidence: 99%
“…These measurements were recorded and processed automatically, and the following parameters were then calculated: volume density (VD = sum of adipocyte area/RA), cell density (CD = number of adipocytes/RA), and cellular size (CS; expressed in lm 2 ). As RA represents the total area were cells were scored, the division of the sum of the individual cell areas by the RA yielded VD, a parameter representing an estimate of cell mass according to generally accepted criteria [40]. The number of cells (CD) was calculated by dividing the immunostained area of the adipose tissue by the mean individual cell area.…”
Section: Experiments 3: Omental Adiposity Characteristics and Functionmentioning
confidence: 99%
“…Both of these hormones are necessary for the development of male and female gonads and are important for the processes of spermatogenesis and oogenesis. Disruption of the function of the hypothalamus may interfere with endocrine functions, including reproductive hormones, thereby affecting the process of folliculogenesis (Camihort, 2004) (Kumalasari, 2012). This study aims to prove whether the antioxidants found in beetroot can increase FSH levels in the ovarie of female white rats.…”
Section: Introductionmentioning
confidence: 99%
“…MSG norvegicus) galur Wistar yang berjumlah 25 ekor yang juga secara nyata berpengaruh pada kerusakan telah sesuai dengan kriteria inklusi. hipotalamus dan hipofise dalam sekresi hormon yang Tempat penelitian dilakukan di Laboratorium Farmakologi berfungsi untuk perkembangan gonad pria dan wanita (2).…”
unclassified